The role of screening for prostate cancer - Jassem, Jacek; Matuszewska, Katarzyna; Matuszewski, Marcin (Contemporary Oncology/Współczesna Onkologia, 2003)
Along with the ageing of the societies, the incidence of prostate cancer is increasing. This malignancy has already become the second most common cancer in men in developed countries. Standard screening methods in prostate cancer include digital rectal examination and evaluation of serum PSA. Other tests like ultrasonography, computer tomography, nuclear magnetic resonance and bone scan are not very useful at early stages of the disease. However, cancer detection in early non-symptomatic phase makes the curative treatment possible. Opponents of the screening claim that a considerable number of screening-detected cases include small, non-aggressive lesions in which a benefit from any form of treatment is doubtful. Given a long natural course of this malignancy and high prevalence of coincident diseases in the elderly population, a benefit from screening in terms of both mortality and costs seems indeed difficult to be proven. Although some studies have already suggested that the screening in this cancer may be beneficial, its real impact on mortality still remains to be established. Meanwhile, strict selection criteria based on the risk factors, potential benefits and general health status of candidates considered for screening should be enforced. Such an approach is particularly relevant in countries like Poland, with a relatively low average life span in men and limited financial resources in the health care system. Hopefully, ongoing randomised screening trials conducted in Europe and in the USA will elucidate the role of screening for prostate cancer within a few years.